If it's not what You are looking for type in the equation solver your own equation and let us solve it.
25-2.5x=3+3x
We move all terms to the left:
25-2.5x-(3+3x)=0
We add all the numbers together, and all the variables
-2.5x-(3x+3)+25=0
We get rid of parentheses
-2.5x-3x-3+25=0
We add all the numbers together, and all the variables
-5.5x+22=0
We move all terms containing x to the left, all other terms to the right
-5.5x=-22
x=-22/-5.5
x=+4
| x+4/2x-1=0 | | |x+4|=|3x-9| | | 3x^2+39x-36=0 | | _2(4a+1)_8=3(2a_1)_7a | | X*(2x+3)-x=3x+5 | | 9+10=x-3 | | 4x=1/2(9x+26-35) | | 6^x=22 | | 3/8w=77/8 | | .7m=6.3 | | 4x+20+2(x–7)=0 | | 5b+12=52 | | 2/3y+3=11 | | 15x=12x+16 | | 2+4+4x15= | | 2x-3(x-2)+8=7 | | 25x-200=3350 | | 5(x+3)=2(5x-5) | | 2x+5x=6x-2x | | 122x*x=x | | -5=x-(-4) | | 0x-x=x | | 4x-(2x-x)=9 | | 8.8^2x=90 | | 6(x-11)=2(3x+8 | | 3(y+6)=8y+15.5y | | 2x+13+6(x-5)=0 | | x-(.2x)=18 | | -3x^2+×^3=4x | | 8x−22=−70 | | -3+8(x-2)=15x+5-7x | | 7(x+3)=4x-3 |